Personality differences in early versus late suicide attempters. Issue 1 (December 2016) - Lewitzka, Ute; Denzin, Sebastian; Sauer, Cathrin; Bauer, Michael; Jabs, Burkhard
Abstract Background Suicidality is an individual behaviour caused by a complex framework of internal and external factors. The predictive values of personality traits for a suicide attempt have been demonstrated, especially in conjunction with Cloninger's TCI and impulsivity. Two issues remain unsolved, namely whether these traits alter over time after a suicide attempt, and how they may be influenced by depressive symptoms. Methods We studied two patient cohorts: one sample of 81 patients after a suicide attempt no longer than 3 months previously (SA early) and another sample of 32 patients whose attempt had taken place more than 6 months previously (SA late). We carried out structured interviews with these subjects addressing diagnosis (MINI), suicidality (Scale for suicide ideation), depression (HAMD-17), temperament and character inventory (TCI), and impulsivity (BIS-10). Data analysis was done using SPSS 16.0. Results Our two groups did not differ significantly in sociodemographics or suicidality. However, patients in the SA early group were significantly more depressed (p < 0.001), and scored lower in reward dependence (p < 0.001 ) and persistence (p = 0.005 ) but higher in harm avoidance (p < 0.001 ); they did not differ significantly in impulsivity (p < 0.01 ). Reward dependence, persistence, and harm avoidance remained significantly different between the two groups after controlling for depressive symptoms. Conclusions Our findings suggest that some personality traits vary after a suicide attempt. Further investigations are necessary to verify our results, ideally in longitudinal studies with larger, carefully-described cohorts. It would be also clinically important to investigate the influence of therapeutic strategies on the variability of personality traits and their impact on suicidal behavior.